Combinatorial design of amorphous TaNiSiC thin films with enhanced hardness, thermal stability, and corrosion resistance. (August 2022) - Kaplan, Maciej; Srinath, Aishwarya; Riekehr, Lars; Nyholm, Leif; Hjörvarsson, Björgvin; Fritze, Stefan
Graphical abstract: Highlights: The peak hardness of the as-grown films was 12.4 GPa and increased 4 GPa after annealing. The TaNiSiC remained amorphous after annealing up to 700 °C for a total of four hours. A few atomic percent of Si significantly increased the corrosion resistance. Separation of Ni and C decrease the resistance to crystallization and material properties. Abstract: Amorphous TaNiSiC and TaNiC films (with varying Ta/Ni and Si/C ratios) were deposited using combinatorial magnetron sputtering. The TaNiSiC films remained X-ray amorphous after four hour-long annealings up to 700 °C, while TaNiC alloys with high Ni and C contents crystallized. These differences were attributed to a strong driving force for separation of Ni and C in TaNiC, whereas the addition of Si, due to its solubility in the other elements, reduced the elemental segregation in TaNiSiC. The as-deposited TaNiSiC films exhibited hardnesses of 9–12 GPa. Annealing led to an increase in hardness by 2–4 GPa, due to decreases in average atomic distance, as evidenced by X-ray diffraction measurements. Potentiodynamic polarizations from –0.7 to +1.5 V vs. Ag/AgCl (3 M NaCl) in 10 mM sodium borate showed lower current densities by up to 2 orders of magnitude with increasing Ta content (28–52 at.%). Changes in Si/C content (7–13 at.% Si) had no effect. However, optical microscopy showed that TaNiSiC films with high Si/low C contents (13/10 at.%) suffered much less localized etching compared to TaNiC films. Thus, Si had a significant role in increasing the mechanical strength, corrosion resistance, and thermal stability of the TaNiSiC films.